Numerical investigation on influence of fuselage on multirotor wake vortex structures in forward flight - Wang, John Chung-Hung (2022)
With the increase interest in utilizing multirotorUAS in very lowaltitude airspace, the safety aspect associated with higher UAS density gains importance. One of the safety consideration is the separation requirements for UAS sharing the airspace, which consists of two major components: wake-based and CNS performance-based. To evaluate thewake-based separation requirements, thewake-field produced by the leadingUAS and the resulting encounter response by the follower UAS must be obtained. While previous studies on aircraft wake vortex evolution showed that the fuselage wake have small impact on the overall wake vortex strength and structures, the more distributed lift generation with less distance between the initial formation point of wake vortex to the fuselage could lead to a larger impact. This paper investigates the impact of including multirotor fuselage on simulating the strength and structure of the resulting wake vortex.